2011
DOI: 10.1016/j.cub.2011.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Socioeconomic Status Predicts Human Ventral Striatal Responses to Social Status Information

Abstract: The enormous influence of hierarchical rank on social interactions [1] suggests that neural mechanisms exist to process status-related information [2] and ascribe value to it. The ventral striatum is prominently implicated in processing value and salience, independent of hedonic properties [3, 4], and a functional magnetic resonance imaging (fMRI) study of social status perception in humans demonstrated that viewing higher-ranked compared to lower-ranked individuals evokes a ventral striatal response [5], indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 11 publications
3
69
1
Order By: Relevance
“…Then, pharmacological inactivation of the NAc indicated the causal involvement of this brain region in social dominance. These findings are in line with previous evidence from lesion (33), neurochemical (34), and pharmacological (35) studies in rodents that highlight a causal involvement of the NAc in the development and/or expression of social dominance, as well as with data from human neuroimaging studies that show NAc activation under tasks involving social competition (21) or manipulation of social status (19,20). Moreover, our findings are in agreement with current views that construe a critical role of the NAc in social operations, ranging from the processing of social information, to learning about conspecifics and making socially influenced decisions (36).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Then, pharmacological inactivation of the NAc indicated the causal involvement of this brain region in social dominance. These findings are in line with previous evidence from lesion (33), neurochemical (34), and pharmacological (35) studies in rodents that highlight a causal involvement of the NAc in the development and/or expression of social dominance, as well as with data from human neuroimaging studies that show NAc activation under tasks involving social competition (21) or manipulation of social status (19,20). Moreover, our findings are in agreement with current views that construe a critical role of the NAc in social operations, ranging from the processing of social information, to learning about conspecifics and making socially influenced decisions (36).…”
Section: Discussionsupporting
confidence: 80%
“…Several brain regions [e.g., the prefrontal cortex (15), NAc (16), and the amygdala (17,18)] have been involved in the establishment of social hierarchies in rodents, with the ventral striatum (including the NAc) being consistently highlighted in human imaging studies of social status (19,20) and competition (21). We confirmed the activation of the nucleus accumbens (along with that of the prefrontal cortex and basolateral, but not central, nucleus of the amygdala) following a social competition test, in both low-and high-anxious naĂŻve animals by comparing the expression of the immediate early transcription factor gene zif-268 mRNA following the encounter to basal conditions (Fig.…”
Section: Significancementioning
confidence: 99%
“…It is worth noting, however, that follow-up studies revealed that these effects are moderated by participants' own socio-economic status (SES). Individuals with lower SES actually showed a greater ventral striatum response to lower-status targets, whereas individuals with higher SES replicated the original finding (Ly, Haynes, Barter, Weinberger, Zink, 2011). This is not surprising in light of the fact that low and high status groups have divergent goals.…”
Section: The Neuroscience Of Social Status Inferencesupporting
confidence: 74%
“…To investigate reward processing, researchers have employed concrete rewards, such as money (Delgado, Nystrom, Fissell, Noll, & Fiez, 2000;Knutson, Adams, Fong, & Hommer, 2001) and food (Kringelbach, O'Doherty, Rolls, & Andrews, 2003;Small, Zatorre, Dagher, Evans, & Jones-Gotman, 2001), and more abstract rewards, such as social status (Ly, Haynes, Barter, Weinberger, & Zink, 2011) and attractive faces Winston, O'Doherty, Kilner, Perrett, & Dolan, 2007). Yet, we note that some reward processing studies have utilized aversive outcomes (e.g., an electrical shock) that subjects aim to avoid (Delgado, Jou, Ledoux, & Phelps, 2009;Kim, Shimojo, & O'Doherty, 2006).…”
Section: Introductionmentioning
confidence: 99%